Novel Behaviors of Southeast Asian Rhacophorid Frogs (Anura, Rhacophoridae) with an Updated Anuran Species List for Danum Valley, Sabah, Malaysian Borneo - SHERIDAN, JENNIFER A.; HOWARD, SAMUEL D.; YAMBUN, PAUL; RICE, JAMES L.; CADWALLADER-STAUB, RACHEL; KAROULUS, ANTHONY; BICKFORD, DAVID (Tropical Natural History, 2012)
Land-use change and the predicted impacts of climate change are major threats to the biodiversity of Southeast Asia. Judging their impacts requires baseline biodiversity data and an understanding of the behavior of resident species in order to effectively manage that diversity. Here, we present an updated anuran species list for Danum Valley Field Center from the results of a nine-week survey expedition. We employed nocturnal stream searches as the basis of sampling and include data gathered from opportunistic encounters. We documented 47 anuran species, including one new locality record. In addition, we recorded a single species of caecilian (Gymnophiona). During this survey period we also documented aggressive territoriality in Rhacophorus appendiculatus, the manipulation of leaves to surround eggs by Rhacophorus pardalis, and predation of an adult Rhacophorus dulitensis by Polypedates otilophus. These observations and their implications are discussed.